ANALISA YURIDIS TERHADAP PENERAPAN PIDANA MATI DI INDONESIA BERDASARKAN APLIKASI ECONOMIC ANALYSIS OF LAW - Darwis, Nurlely (JURNAL ILMIAH HUKUM DIRGANTARA, 2018)
The current death penalty is a controversial issue from many perspectives. A view holds that the death penalty is an appropriate punishment for a particular crime with a deterrent effect, but another view suggests that the death penalty is a violation of human rights, because everyone has a right to life that no one can and can not under any circumstances. The Indonesian government's opinion in favor of the death penalty for drug offenses believes that this type of punishment can reduce crime. As emphasized by President Joko Widodo, at least 50 people die every day in Indonesia because drug use for the death penalty is believed to be an effective way to reduce the impact of drugs, and to prevent young people from engaging in drug use and abuse. In this case, it is better to "kill" a handful of people, in order to save more Lies.